THE RESEARCH OF THERMOSYPHONS FUNCTIONING AT PROCESSING OF DISPERSED AND VISCOUS FOOD MEDIUMS - Bezbah I.V.; Omer Seed Ahmed; Donkoglov V. I. (Problems of the Regional Energetics, 2009)
Devices based on thermosyphons for drying, heat treatment of disperse food materials, non-Newtonian food liquids are considered. The results of experimental researches are shown.